HUBUNGAN KARAKTERISTIK TERHADAP PENGETAHUAN DAN SIKAP KADER KESEHATAN TENTANG PENTINGNYA DATA DI BUKU KIA - Yudhy Dharmawan (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Infant Mortality in Indonesia still high . It is could have been avoided with good management of MCH services.  To  achieve  good  management  activities,  it  is  necessary  availability  data  from  surveillance activities in the community. The data is sourced in the MCH handbook. Cadre very important role in the completeness and validity of data captured in the MCH handbook. Knowledge and attitudes cadres determine  the  data  recording  in  the  MCH  handbook.  Therefore  it  is  important  to  know  what  are  the factors  that  influence  the  knowledge  and  attitudes  about  the  importance  of  data  Kader  KIA.  The research  method  used  survey  approach  by  looking  at  the  relationship  between  age,  education  and length of employment with the attitude and knowledge of cadres. Results showed characteristic Cadres of  the  age,  including  adulthood,  with  most  respondents  education  is  the  primary  level. length  of employment been a cadre mean is 8.06 years. Most of the knowledge and attitudes of the respondents about the importance of data MCH very good ,. There is a significant and positive relationship between education with the knowledge and attitudes about the importance of data MCH. There is a significant relationship between age and in contrast with the attitude of the cadres of the importance of data MCH. There is no relationship between the old cadre with knowledge and attitudes about the importance of data KIA cadre. It is advisable to pay attention to the education cadre recruitment. Keywords: Health Cadre, Data, Book KIA